Potential Benefits and Challenges of Integrating Risk Management with Stakeholder Management: Case Study on Gold Processing Plant Construction Project in Central Sulawesi, Indonesia - Siti Zubaidah Chaidir; Arief Bimantoro Suharko (CV. Publikasi Indonesia, 2024)
The purpose of this study is to examine the potential benefits, challenges, and dynamics of implementing the integration of Risk Management (RM) and Stakeholder Management (SM) on a Gold Processing Plant Construction Project in Central Sulawesi, Indonesia. The method used is qualitative approach using the grounded theory method, with primary data from stakeholder interviews and secondary data from literature studies. The results show that Relationship Mode 3, i.e. Management of Stakeholder Differences Concerning Risk, is most applicable, as it improves conflict management and risk response strategies. Recommendations include the integration of this mode into the financial model as a risk management system.